The care ceiling in higher education - Lynch, Kathleen; Ivancheva, Mariya; O'Flynn, Micheál; Keating, Kathryn; O'Connor, Monica (Irish Educational Studies, 2020)
This study examines the impact of managerialist policies on care relations in higher education. It is based on a study of 10 higher education institutions in Ireland. The paper shows that a care-free worker model is ingrained in systems of performance appraisal, especially for academics in universities, and increasingly in the Institutes of Technology, although it also impacts on support staff in other professions and occupations. It assumes a life of boundary-less working hours and unhindered mobility. The market-informed tools of performance appraisal, especially audits and metrics, cannot measure essential care work because care is a process and disposition, not a product. Because it is not countable caring becomes invisible as do the people who do it. The managerial ideology of 'work–life balance' merely operates as a mask that conceals how over-working is normalised. There is no legitimate language to name over-working for the structural problem that it is. When work organisations disregard care commitments outside of work, and even within it, these are then repackaged and fed back to women/carers as personal problems and failures. The idealised care-free worker model operates as a care ceiling over women particularly; it is taken as given, even natural.
Keywords: 2000 à aujourd'hui; approches et analyses; care; charge mentale; conciliation famille-travail; europe; famille; femmes universitaires*; irlande; patriarcat; politiques néolibérales; projet charge mentale; périodes historiques; rapports sociaux de sexe; rentabilité; régions géographiques; systèmes d'oppressions; thématiques; travail; travail du care